2003
DOI: 10.1016/s0377-1237(03)80004-7
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence after Posterior Sagittal Anorectoplasty – Follow up of 2 years

Abstract: After an anorectal malformation (ARM) is repaired, the goal is fecal continence of the patient. Toilet training is not complete in children below 4 years of age. Manometric and radiological studies need cooperation of the child, and are therefore of little value during the critical preschool years. In this present study, we used only clinical criteria to assess the child for constipation and incontinence after definitive operation. We included all patients of ARM wef 01 April 1998 to 31 March 2000. Only 2 chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…On this issue there are different standpoints of different authors. Traditionally, it has been said that one has to wait 12 to 13 years before one can have a real evaluation of patients subjected to a repair of an anorectal malformation [18]. On the other hand Kiely and Pena do not believe that children have better fecal control as time passes [19].…”
Section: Chartmentioning
confidence: 99%
“…On this issue there are different standpoints of different authors. Traditionally, it has been said that one has to wait 12 to 13 years before one can have a real evaluation of patients subjected to a repair of an anorectal malformation [18]. On the other hand Kiely and Pena do not believe that children have better fecal control as time passes [19].…”
Section: Chartmentioning
confidence: 99%
“…The prevalence of fecal and urinary incontinence following posterior sagittal anorectoplasty for anorectal malformation has been widely observed and assessed, with many variations; according to a study by Ghorbanpoor et al, good fecal continence was observed in 91.3% of patients with low type anorectal malformation compared to 72.8% of patients with high type anorectal malformation; however, the difference was not significant [ 13 ]. Furthermore, researchers discovered that incontinence was less common in low abnormalities and more common in high or intermediate anomalies, whereas constipation was more common in low anomalies and less common in high and intermediate anomalies, according to Harjai et al Thirty-one percent of the patients born with anorectal abnormalities who had posterior sagittal anorectoplasty (PSARP) were completely continent, 38% experienced fecal soiling, and 31% had constipation difficulties [ 14 ].…”
Section: Discussionmentioning
confidence: 99%